Expression of MDR1/P glycoprotein in human sarcomas. - Vergier, B. (Nature Publishing Group, 1993)
Conflicting reports of MDR1 gene expression in human tumours are observed according to whether studies are performed at the mRNA or P-glycoprotein level. We have investigated this expression in 22 clinically drug-resistant sarcomas at the mRNA level by Northern blot (NB), Dot blot (DB), in situ hybridisation (ISH), and at the protein level by immunohistochemistry (IHC) using three monoclonal antibodies (MoAbs): C219, JSB1, MRK16. Increased MDR1 mRNA expression was detected by NB, DB, and ISH in 1/22 sarcoma (an Ewing's sarcoma). ISH was perfectly correlated with DB hybridisation and confirmed the expression of tumoral cells alone. Specific staining of 100% of tumoral cells was obtained with the three MoAbs in the same sarcoma. Expression in tumoral cells of 12 other sarcomas was detected with MRK16, and positive staining of stromal cells with both C219 (1/22) and MRK16 (8/22) was observed. This study confirms that MDR1 overexpression occurs in human sarcomas but is not the principal mechanism of drug-resistance. Furthermore, positivity with one antibody does not necessarily imply the presence of P glycoprotein (P-gp) and a disparity may exist between the levels of P-gp and its mRNA in the same sample. So care must be taken in interpreting results and more sensitive techniques such as the polymerase chain reaction (PCR) could prove useful. IMAGES: